Bronchopleural fistula secondary to tuberculosis: A rare presentation with diagnostic challenges - Nor Amal Lina Shamsudin; Yap, Yoon Chin; Lo, Zhen Zhen (Elsevier Inc, 2025)
Tuberculosis (TB) remains a prevalent disease in developing countries, with a wide range of pulmonary and extrapulmonary manifestations. Among its complications, tuberculosis-induced bronchopleural fistula (BPF) is rare but poses significant diagnostic and therapeutic challenges.1 This case highlights the diverse clinical presentations of TB-BPF and the importance of considering this condition in the differential diagnosis of patients with persistent air leaks and pneumothorax, especially in TB-endemic regions.